PHOTODYNAMIC THERAPY: A LIGHT OF HOPE IN FIGHT AGAINST CANCER - Samanamú Ch., Christian (2003)
Currently, photodynamic therapy is one of the most promising for the treatment of cancer treatments. This article describes the basic principles of this therapy are explained and a review of the main types of existing photosensitizers currently is performed, with emphasis on those derived from porphyrins and phthalocyanines.